The psychological skill characteristics of Indonesian volleyball players from player positions - Pulungan, Khoirul Anwar; Perdana, Satya; Haryanto, Arief Ibnu; Haryani, Meri; Kadir, Sulasikin Sahdi (Jurnal Keolahragaan, 2023)
This study means to decide: (1) the characteristics of the psychological capacities of Indonesian volleyball players, (2) the nature of the psychological capacities of Indonesian volleyball players concerning what is going on. The kind of investigation utilized in this test is enlightening quantitative investigation, utilizing a procedure survey. with a causal-like survey focusing on the arrangement. The populace in this study were Indonesian volleyball players who participated in the eighteenth Asian Games in 2018 in Indonesia adding up to 28 Indonesian players comprising of 14 male players and 14 female players, with a commonplace time of male volleyball players matured 25 years and normal football players. volleyball. The assortment of data on volleyball for ladies matured 20 purposes The Psychological Skills Inventory for Sport (PSIS) survey. The data checking system utilizes inferential parametric estimations utilizing a one-way ANOVA test for contrast planning, with a significance level of 0.05. These outcomes show: (1) The nature of the psychological capacities of Indonesian people's volleyball players taking part in the 2018 XVIII Asian Games are for the most part in the high and medium grouping, with a common score of 142.92 independently for men and a regular score for ladies of 126, 9; (2) There is no monstrous difference in the psychological expertise credits of Indonesian volleyball players in regards to position, with the worth of Sig. 0.930 > 0.05